Apparel Shopping Styles of Young Adult Consumers in Bangalore - Vincent, Theresa Nithila (Indian Journal of Marketing, 2016)
Apparels are one of the most frequently purchased product categories where young adults have the authority to make independent buying decisions, and they also become trendsetters and opinion leaders. Understanding this large segment appropriately is crucial for apparel manufacturers and marketers as they promise longevity of market and exert substantial influence on their parents, peers, as well as their own spending. The present study segmented young adult consumers based on their shopping styles towards purchase of apparels and explored the differences in the shopping styles across demographics such as gender, educational levels, and regional background. The respondents for the study were young adults who belonged to the age group of 18 - 25 years residing in Bangalore, India. The variables under study were eight shopping styles adapted from Sproles and Kendall Consumer Style Inventory- CSI (1986). The study revealed that all the eight shopping styles of the CSI were manifested among young adults in Bangalore; however, the predominant shopping style was the Perfectionist/ High Quality Conscious shopping style. Furthermore, significant differences in the shopping styles of young adults across gender, educational levels, and regional background were found.